Regional differences in presentation characteristics, use of treatments and outcome of patients with cardiogenic shock: Results from multicenter, international registry - Michal Pazdernik (Palacký University Olomouc, Faculty of Medicine and Dentistry, 2021)
Background. Concurrent evidence about cardiogenic shock (CS) characteristics, treatment and outcome does not represent a global spectrum of patients and is therefore limited. The aim of this study was to investigate these regional differences. Methods. To investigate regional differences in presentation characteristics, treatments and outcomes of patients treated with all types of cardiogenic shock (CS) in a single calendar year on a multi-national level. Consecutive patients from 19 tertiary care hospitals in 13 countries with CS who were treated between January 1, 2018 and December 31, 2018 were enrolled in this study. Results. In total, 699 cardiogenic shock patients were included in this study. Of these patients, 440 patients (63%) were treated in European hospitals and 259 (37%) were treated in Non-European hospitals. Female patients (P<0.01) and patients with a previous myocardial infarction (P=0.02) were more likely to present at Non-European hospitals; whereas older patients (P=0.01) and patients with cardiogenic shock due to acute heart failure (P<0.01) were more likely to present at European hospitals. Vasopressor use was more likely in Non-European hospitals (P=0.04), whereas use of mechanical circulatory support (MCS) was more likely in European hospitals (P<0.01). Despite adjustment for relevant confounders, 30-day in-hospital mortality risk was comparably high in CS patients treated in European vs. Non-European hospitals (hazard ratio 1.08, 95% CI 0.84-1.39, P=0.56). Conclusion. Despite marked heterogeneity in characteristics and treatment of CS patients, including fewer use of MCS but more frequent use of vasopressors in Non-European hospitals, 30-day in-hospital mortality did not differ between regions.